Pedagogical Conditions for the Formation of Information and Communication Competence in Future Teachers of Music - Zhang, Gege (Pedagogical Discourse, 2024)
The advent of information and communication technologies has had a profound impact on the field of education, particularly in the domain of arts education. For those aspiring to become music educators, the ability to engage effectively with information and communication technologies is paramount. This is because such competencies enhance interaction in the educational process, support innovative teaching methods, and enrich artistic-pedagogical activities. This competence is vital for integrating digital tools into music education, improving learning experiences, and achieving various educational goals. The relevance of this issue is highlighted by several factors. The evolution of educational standards necessitates that prospective educators possess the capacity to utilize information and communication technologies, as delineated by frameworks such as the New Ukrainian School and the European Qualifications Framework. Furthermore, the integration of advanced technologies in music pedagogy is being encouraged by the advent of digitalization, thus fostering creativity and enhancing teaching methods. The evolving role of teachers now requires them to function as facilitators and mentors, which demands high digital literacy and communication skills, especially in online environments (Varnavska, L., Viktorova, M., & Rymar, L. (2021), 4-7). The global challenges posed by the ongoing pandemic and the ongoing war in Ukraine have served to underscore the necessity for distance and blended learning models, particularly in the domain of arts education where interactivity and audiovisual content are imperative. It is therefore timely and crucial to explore the pedagogical conditions for developing information and communication competence in future music educators, with a view to improving arts education and preparing competitive professionals. This article investigates the pedagogical conditions for developing information and communication competence in future music educators. The paper establishes and describes in detail the key pedagogical conditions for the formation of information and communication competence of future music teachers. These conditions include the development of the motivational and value sphere of future music teachers, the integration of music-pedagogical and information and communication training, interdisciplinary training and self-development of digital literacy of future music teachers aimed at self-development of the individual. The implementation of these conditions has been shown to assist in the cultivation of students’ technical and creative skills, while concurrently promoting critical thinking and problem-solving abilities. The article presents a comprehensive approach to teacher training, emphasizing motivation, teacher preparedness, and the integration of information and communication technologies. In the context of ongoing digital transformation in education, it is imperative that music educators possess the competencies to navigate this evolving landscape. This research offers valuable insights for educators, policymakers, and researchers working to improve arts education in the digital era.